A Review on Gravity Power Generation (International Journal of Advanced Research in Science, Management and Technology, 2020)
Gravitational vitality is the vitality where a question has descending development as a result of its weight in a gravitational field. The most well-known utilization of gravitational potential vitality is for a protest close to the surface of the Earth where the gravitational quickening can be thought to be steady at around 9.8 m/s. Since the zero of gravitational potential vitality can be picked at any point(like the decision of the zero of a facilitate framework), the potential vitality at a tallness h over that indicate is equivalent the work which would be required to lift the protest that stature with no net change in active vitality. Since the constrain required to lift it is equivalent to its weight, it takes after that the gravitational potential vitality is equivalent to its weight times the tallness to which it is lifted.
Keywords: : Gravitational vitality, gravitational field, gravitational potential